Prevalence of anti-diabetic medication adherence and determinant factors in Ethiopia: A systemic review and meta-analysis, 2019 - Kassahun Gebeyehu Yazew; Tarkie Abebe Walle; Abere Woretaw Azagew (Elsevier, 2019)
Background: Adherence to antidiabetic medication is the challenge in diabetes treatment. However, from Ethiopia, there are some studies with variability and inconsistency findings. Therefore, the aim of this study was to estimate the pooled prevalence of anti-diabetic medication adherence among diabetic patients in Ethiopia. Methods: In this systematic review and meta-analysis, we intensely searched PubMed, Google Scholar, Science Direct and Google. To assess the pooled prevalence, studies describing the prevalence of anti-diabetic medication adherence and its determinants were included. Data were extracted by a standardized data extraction format prepared in Microsoft Excel and transferred to STATA 11 statistical software for analysis. Cochrane Q test statistics and I2 test were used to check heterogeneity. Studies were exhibited considerable heterogeneity, so a random effect model was used to the Poole prevalence of anti-diabetic medication adherence. Finally, the link between the factors and anti-diabetic medication adherence was assessed. Results: The pooled prevalence of adherence of the anti-diabetic medication in Ethiopia, was 69.5% (95% CI (61.1, 78.0)). The subgroup analysis of this study showed that the highest prevalence was from SNNP region, 88.2% (95% CI: 80.5, 95.9%), followed by studies in Addis Ababa 78.7% (95% CI: 68.8, 88.5). Older age (OR: 1.8, 95% CI: (1.3, 2.6)) and rural residence (OR: 4.9: 95% CI: (1.7, 14.0)) were found to be determinants of anti-diabetic adherence. Conclusion: The overall pooled prevalence of anti-diabetic adherence in Ethiopia, was somewhat low. Age and rural residency were the main determinants of anti-diabetic adherence in Ethiopia.